Evaluation of empathy and biopsychosocial approaches of medical faculty assistant doctors - Ebru Cicek; Ahmet Yilmaz; Hamza Aslanhan (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION AND AIM: Biopsychosocial approach suggests that the individual's health condition is partly influenced by the interactions of biological, psychological, and social processes. It also concludes that the clinical method should be patient-centered, which is based on the physician's involvement in the patient's world and the physician's ability to see the illness from the patient's view. In this study, we aimed to determine the extent to which medical faculty assistant doctors use the biopsychosocial approach in their clinical practice. MATERIALS AND METHODS: Our study is a cross-sectional type, descriptive, and analytical research. The sample size consisted of assistant doctors who met the inclusion criteria which were accepted to participate in the study between December 1, 2017, and March 1, 2018, at the medical faculty hospital of Dicle University. Two hundred and three physicians participated in our study. The Patient-Physician Orientation Scale (PPOS), The Jefferson Scale of Physician Empathy (JSPE), and a survey study including questions in relation with sociodemographic characteristics were conducted in our study. The reliability of the Patient-Physician Orientation Scale (PPOS) and JSPE used in our study was tested with Cronbach's alpha and found to be 0.878 and 0.931, respectively. Questionnaires were administered by a face-to-face interview method during interview. Information on the purpose and method of the study was given. RESULTS: A total of 203 physicians participated in our study. One hundred and forty-three (70%) participants were male and 60 (30%) were female. According to medical disciplines, eight physicians (3, 9%) from psychiatry, 21 (10, 3%) from family medicine, 104 (51, 2%) from other internal medical disciplines, and 70 (34, 5%) from surgical medical disciplines participated in the study. In the first subgroup of the PPOS, which is used in our study, the average score of psychiatry physicians was 3.67 ± 0.99, family medicine assistant doctors 3.92 ± 0.67, other internal medical disciplines 3.98 ± 0.65, and surgical medical discipline 3.83 ± 0.61. In the second subgroup, which is defined as the care in the same scale, the average score of psychiatry assistant doctors was found to be 3.20 ± 0.45, family medicine assistant doctors 3.68 ± 0.54, other internal medical disciplines 3.49 ± 0.60, and surgical medical discipline 3.68 ± 0.58. The results of the Jefferson Scale used to determine the level of empathy in our study are found as psychiatry 78.25 ± 14.78, family physician 67.71 ± 14.69, other internal medical disciplines 72.03 ± 13.46, and surgical medical discipline 70.87 ± 15.24. CONCLUSIONS: The biopsychosocial approach is primarily an elementary approach model in medical discipline such as family medicine and should be applied to other internal and surgical medical disciplines as well. With conducting this study, the awareness of this area will be increased and related issues in the literature will be enriched.